Cultural Belief of Arranged Marriage as Patriarchy System Towards Freedom of Choice in I am Nujood, Age 10 and Divorced by Minoui Delphine (Prologue: Journal on Language and Literature, 2022)
This research is focused on the cultural belief of arranged marriage as a patriarchal system toward freedom of choice in I am Nujood, Age 10 and Divorced by Delphine Minoui. This research aims to identify the obstacles to a cultural belief in an arranged marriage in the novel and to reveal the effect of obstacles to arranged marriage on woman’s freedom. The purpose of this research is to reveal the cultural belief about arranged marriage in Yemen society and to determine the effect of arranged marriage. The methodology employed is descriptive qualitative. As for the data, the primary data is from the novel. Secondary data in this study contains the text that supports the theories such as: cultural studies, supporting theory radical feminism and feminism existentialism from books, e-books, thesis and journals. The result of this research is the main characters reveal the cultural belief of arranged marriage happened in Yemen is the obstacle that makes the main character decide to get her freedom of choice.